OPTIMIZING THE ACOUSTIC CONDITION OF A PYRAMIDAL-CEILING MOSQUE BASED ON SIMULATION - Radhiyah Ulfah Pratiwi; Anugrah Sabdono Sudarsono; Zaenal Muttaqin; Supriyanto Supriyanto (Journal of Islamic Architecture, 2023)
This study aims to optimize the acoustic condition of a pyramidal ceiling mosque utilizing a simulation approach. The simulation was done using I-Simpa, simulating the room acoustic parameters of 15 m x 15 m x 5 m and a 5 m roof height of a mosque. The optimization was accomplished by varying the occupancy level and using absorbent materials. The best acoustic condition was defined as having a high level of speech intelligibility (C-50 > -2 dB) yet the longest possible reverberation time, especially at 500-4000 Hz. The simulation indicates that the speech intelligibility value increases with the number of filled rows, both with and without sound-absorbing material. On the other hand, the reverberation time is unaffected by the number of filled rows and is extended by using sound-absorbing materials. Hence, without sound-absorbing ceiling material, optimal conditions are attained when the mosque is fully occupied. Meanwhile, using sound-absorbing materials on the mosque's ceiling establishes optimal acoustic conditions for all occupancy levels. It demonstrates that using sound-absorbing materials improves the acoustic quality of the pyramidal-ceiling mosque.